(3CSSgG GdfXQjI h HfGA bhGYO HjGfGJgGs - (3UHGM QMjeI(B, (3eMSfs; (3YHO GdaJGM GHQGgje RQjHI(B, (3aJMj CMeO GdTjHGfjs ((3YeGf(B:s (3GdhQGb ddfTQ hGdJhRjY(B,s, 2011)
(3fXe GdeYdheGJ HUaI YGeI , fXe OYe GdbQGQGJ h fXe eYdheGJ GdGfJGL , fXe GdeYdheGJ GdeGdjI , HfGA bhGYO HjGfGJ ZSjd GdCehGd h HfGA bhGYO HjGfGJ eGdjIs
(3bGFeI GdLOGhd U(B.09(3; bGFeI GdGTcGd U(B.11s
Keywords: (3GdeGdjI GdYGeIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s; (3fXe GdeYdheGJ(B- (3GdeGdjIs